Combination of autochthonous Lactobacillus strains and trans-Cinnamaldehyde in water reduces Salmonella Heidelberg in turkey poults - Dewi, Grace; Manjankattil, Shijinaraj; Peichel, Claire; Johnson, Timothy J.; Noll, Sally; Cardona, Carol; Kollanoor Johny, Anup (Frontiers in Microbiology, 2024)
Reducing the colonization of Salmonella in turkeys is critical to mitigating the risk of its contamination at later stages of production. Given the increased susceptibility of newly hatched poults to Salmonella colonization, it is crucial to implement interventions that target potential transmission routes, including drinking water. As no individual intervention explored to date is known to eliminate Salmonella, the United States Department of Agriculture-Food Safety Inspection Service (USDA-FSIS) recommends employing multiple hurdles to achieve a more meaningful reduction and minimize the potential emergence of resistance. Probiotics and plant-derived antimicrobials (PDAs) have demonstrated efficacy as interventions against Salmonella in poultry. Therefore, this study aimed to investigate the use of turkey-derived Lactobacillus probiotics (LB; a mixture of Lactobacillus salivarius UMNPBX2 and L. ingluviei UMNPBX19 isolated from turkey ileum) and a PDA, trans-cinnamaldehyde (TC), alone and in combination (CO), against S. Heidelberg in turkey drinking water and poults. The presence of 5% nutrient broth or cecal contents as contaminants in water resulted in S. Heidelberg growth. TC eliminated S. Heidelberg, regardless of the contaminants present. In contrast, the cecal contents led to increased survival of Lactobacillus in the CO group. Unlike TC, LB was most effective against S. Heidelberg when the nutrient broth was present, suggesting the role of secondary metabolites in its mechanism of action. In the experiments with poults, individual TC and LB supplementation reduced cecal S. Heidelberg in challenged poults by 1.2- and 1.7-log10 colony-forming units (CFU)/g cecal contents, respectively. Their combination yielded an additive effect, reducing S. Heidelberg by 2.7 log10 CFU/g of cecal contents compared to the control (p ≤ 0.05). However, the impact of TC and LB on the translocation of S. Heidelberg to the liver was more significant than CO. TC and LB are effective preharvest interventions against S. Heidelberg in poultry production. Nonetheless, further investigations are needed to determine the optimum application method and its efficacy in adult turkeys.